Preparation and Study Hardness and Thermal Conductivity (Tc) to Polyester Resin Composite with (Titanium Dioxide, Zinc Oxide, Acrylonitril, Wood Flour Coconut (Baghdad Science Journal, 2025)
This study is attempt to improve thermal isolation through measuring thermal conductivity composite of on polyester resin with fillers of (TiO2, ZnO, Acrylonitril, wood flour Coconut (Wf). The grain size of the fillers is 200 µm. The number of samples is (16) in addition to the virgin sample; these samples are prepared by cast molding method for polyester with filler volume fractions (5%, 10%, 15% and 20%). Shore hardness tests were used to measure the hardness and Lee disk method for thermal conductivity. The experimental results showed that the (20% ZnO) sample has the maximum value of thermal conductivity where (20% w.f) has minimum thermal conductivity .on the other hand (15% ZnO) sample give the maximum value of hardness where (20% w.f) sample gave the minimum value of hardness. From this study there is an important factor that should be observed that is the relationship between hardness and thermal conductivity. The study prove that the experimental results satisfy the theoretical assumptions in that the additive material (fillers) of metals base increase thermal conductivity where the material of cellulose base decrease the thermal conductivity and give good thermal isolation but with low hardness and all the result above the refry sample .